2007
DOI: 10.1007/s00572-006-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi can induce the production of phytochemicals in sweet basil irrespective of phosphorus nutrition

Abstract: The potential of three arbuscular mycorrhizal fungi (AMF) to enhance the production of antioxidants (rosmarinic and caffeic acids, RA and CA) was investigated in sweet basil (Ocimum basilicum). After adjusting phosphorus (P) nutrition so that P concentrations and yield were matched in AM and non-mycorrhizal (NM) plants we demonstrated that Glomus caledonium increased RA and CA production in the shoots. Glomus mosseae also increased shoot CA concentration in basil under similar conditions. Although higher P ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
138
7
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(164 citation statements)
references
References 36 publications
16
138
7
3
Order By: Relevance
“…Consequently, AM symbiosis can enhance the synthesis of certain amino acids and contribute to the accumulation of specific metabolites by promoting N uptake (Smith and Read 1997;Toussaint et al 2004). Some research has also shown that symbiosis with AM fungi results in the increase of terpenoids and phenolic acids, which may result from increased absorption of mineral nutrients, especially P and N (Kapoor et al 2002a, b;Toussaint et al 2007). Finally, changes in the secondary metabolites of mycorrhizal plants may result from changes in levels of phytohormones like cytokinin or gibberellin (Allen et al 1980(Allen et al , 1982Copetta et al 2006;Kapoor et al 2007;Toussaint 2007).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, AM symbiosis can enhance the synthesis of certain amino acids and contribute to the accumulation of specific metabolites by promoting N uptake (Smith and Read 1997;Toussaint et al 2004). Some research has also shown that symbiosis with AM fungi results in the increase of terpenoids and phenolic acids, which may result from increased absorption of mineral nutrients, especially P and N (Kapoor et al 2002a, b;Toussaint et al 2007). Finally, changes in the secondary metabolites of mycorrhizal plants may result from changes in levels of phytohormones like cytokinin or gibberellin (Allen et al 1980(Allen et al , 1982Copetta et al 2006;Kapoor et al 2007;Toussaint 2007).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Treating cough and headache Gupta et al 2002;Karagiannidis et al 2011 Ocimum basilicum Treating trauma and snake bite Copetta et al 2006;Toussaint et al 2007;Lee and Scagel 2009;Prasad et al 2011;Rasouli-Sadaghianil et al 2010 Origanum sp. Appetitanregend, promoting digestion, antibacterial effect Khaosaad et al 2006 Origanum vulgare Appetitanregend, promoting digestion, antibacterial effect…”
Section: Mentha Arvensismentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the production of secondary compounds in plants associated with AMF may be due to the increased nutritional supply (Toussaint et al, 2007), hormonal changes, enzymatic activation (Zhang et al, 2013) and increased activity of plastidial and mitochondrial pathways (Lohse et al, 2005), however, the effects seem to be somatory and multifactorial (Toussaint et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such organisms are obligatory symbionts because they complete their life-cycle only in the presence of a host plant (Souza et al, 2008). After the fungus has established on the root, the AMF absorb (Smith and Read, 2008).Various studies relate the benefits of mycorrhizal association with legumes and point out the increased vegetable growth and optimized production of primary (Manoharan et al, 2010) and secondary metabolites (Silva et al, 2014a;Nisha and Rajeshkumar, 2010;Kapoor et al, 2004).The increase in the production of secondary compounds in plants associated with AMF may be due to the increased nutritional supply (Toussaint et al, 2007), hormonal changes, enzymatic activation (Zhang et al, 2013) and increased activity of plastidial and mitochondrial pathways (Lohse et al, 2005), however, the effects seem to be somatory and multifactorial (Toussaint et al, 2007).The Caatinga is a biome that is rich in leguminous species with medicinal properties that are widely used by the local population as phytotherapeutic drugs (Agra et al, 2007(Agra et al, , 2008. Amburana cearensis is found among the medicinal plants of the Caatinga, a legume that is used by the local population.…”
mentioning
confidence: 99%